2007
DOI: 10.3346/jkms.2007.22.4.677
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance Rates of Mycobacterium tuberculosis at a Private Referral Center in Korea

Abstract: The goals of this study were to identify first-line drug resistance in new and previously treated tuberculosis (TB) cases and to determine risk factors for multidrug-resistant TB (MDR-TB) at a private referral center in Korea. All patients with culture-confirmed pulmonary TB over a 2-yr period between July 2002 and June 2004 were prospectively included in this study. In total, 637 patients were included; 512 (80.4%) were new cases, and 125 (19.6%) were previously treated cases. Resistance to at least one first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 20 publications
2
25
2
Order By: Relevance
“…Previous treatment of tuberculosis has been consistently reported as the risk factor within various clinical conditions and populations. 12,13,14,15 The present study also revealed that previous treatment of tuberculosis (n=285, 98.95%) was strongly associated with MDR TB. A reported history of previous treatment of tuberculosis, although unconfirmed, suggests that MDR-TB was acquired during a previous treatment episode; such acquired drug resistance may indicate failure of TB control efforts due to inadequate case management, interruptions in drug supply, or inadequate drug regimens.…”
Section: Discussionsupporting
confidence: 52%
“…Previous treatment of tuberculosis has been consistently reported as the risk factor within various clinical conditions and populations. 12,13,14,15 The present study also revealed that previous treatment of tuberculosis (n=285, 98.95%) was strongly associated with MDR TB. A reported history of previous treatment of tuberculosis, although unconfirmed, suggests that MDR-TB was acquired during a previous treatment episode; such acquired drug resistance may indicate failure of TB control efforts due to inadequate case management, interruptions in drug supply, or inadequate drug regimens.…”
Section: Discussionsupporting
confidence: 52%
“…An increasing number of cases of XDR TB are being reported globally [29]. In Korea, 15%-20% of patients with MDR TB meet the criteria for XDR TB in both the public and private sector [7,30,31]. Recently published studies have demonstrated that the occurrence of XDR TB is an independent poor prognostic factor in HIV-uninfected patients with MDR TB [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we could not find a prophylactic effect of anti-TB medications; 12.5% (2/16) of patients with LTBI who took prophylactic anti-TB medication still developed active TB, whereas 14.3% (2/14) of patients with LTBI who did not take prophylaxis had active TB during anti-TNF therapy (Figure 1). Although the exact reason for the lack of efficacy of prophylaxis in this study is unclear, the emergence of drug-resistant TB in Korea might be a possible explanation [31,32] . Guidelines recommend delaying to begin anti-TNF for at least 3 wk when LTBI is confirmed [16,33] .…”
Section: Incidence and Risk Factors Of Active Tb Infection After Antimentioning
confidence: 99%